Tailoring electronic properties and kinetics behaviors of Pd/N‐CNTs catalysts for selective hydrogenation of acetylene. Issue 4 (29th November 2019) - Cao, Yueqiang; Fu, Wenzhao; Ren, Zhouhong; Sui, Zhijun; Zhou, Jinghong; Luo, Jun; Duan, Xuezhi; Zhou, Xinggui
Abstract: Pd catalyzed selective hydrogenation of acetylene shows remarkable electronic effects. In this work, a strategy is proposed to tailor the electronic properties of Pd nanoparticles by nitrogen doping of carbon nanotubes (CNT) support toward the improved reaction kinetics. While excluding the Pd size effects, the intrinsic promotional effects of the nitrogen doping are demonstrated, which are mainly due to the increased Pd electron density resultant from the presence of more graphitic nitrogen species based on X‐ray photoelectron spectroscopy measurements and density functional theory (DFT) calculations. Kinetics analysis and C2 H2 /C2 H4 ‐temperature‐programmed desorption (TPD) measurements reveal that the electron‐rich Pd catalyst with the moderately weakened adsorption strength can give rise to the decreased activation energy and thus the simultaneously enhanced activity, selectivity, and stability. The aspects demonstrated here could guide the rational design and optimization of Pd catalysts for the selective hydrogenation of acetylene.